(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To synthesize existing evidence on the antibacterial effectiveness of the QMix root canal irrigant against Enterococcus faecalis. Methods: A scoping review was conducted in accordance with the PRISMA-ScR guidelines, using a systematic search of the PubMed and Cochrane databases. In vitro studies evaluating the antibacterial activity of QMix against E.faecalis and including comparisons with other root canal irrigants were included in the analysis. Results: After screening, 11 studies met the inclusion criteria and were analyzed. QMix demonstrated significant antibacterial activity against E.faecalis. When compared with sodium hypochlorite, its effectiveness was inconsistent and influenced by irrigant concentration, volume, and contact time. QMix showed comparable efficacy to chlorhexidine and superior antibacterial activity compared with ethylenediaminetetraacetic acid under most experimental conditions. Conclusion: QMix exhibits favorable antibacterial activity against E.faecalis and may serve as a promising adjunctive irrigant in endodontic treatment.